Platelet Transcriptome Profiling in HIV and ATP-Binding Cassette Subfamily C Member 4 (ABCC4) as a Mediator of Platelet Activity - Emanuela Marcantoni, PhD; Nicole Allen, BS; Matthew R. Cambria, BA; Rebecca Dann, BS; Michael Cammer, BS; Tenzin Lhakhang, BS; Meagan P. O’Brien, MD; Benjamin Kim, BS; Tilla Worgall, MD, PhD; Adriana Heguy, PhD; Aristotelis Tsirigos, PhD; Jeffrey S. Berger, MD, MS (JACC: Basic to Translational Science, 2018)
An unbiased platelet transcriptome profile identified ATP binding cassette subfamily C member 4 (ABCC4) as a novel mediator of platelet activity in virologically suppressed human immunodeficiency virus (HIV)-infected subjects on antiretroviral therapy. Using ex vivo and in vitro cellular and molecular assays we demonstrated that ABCC4 regulated platelet activation by altering granule release and cyclic nucleotide homeostasis through a cAMP-protein kinase A (PKA)–mediated mechanism. Platelet ABCC4 inhibition attenuated platelet activation and effector cell function by reducing the release of inflammatory mediators, such as sphingosine-1-phosphate. ABCC4 inhibition may represent a novel antithrombotic strategy in HIV-infected subjects on antiretroviral therapy.